(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article analyzes the symbolic and cognitive characteristics of flower names in contemporary Uzbek poetry based on the works of Uzbek poet Enakhon Siddiqova. The article examines flower names as poetic symbols, conceptual metaphors, and expressions of feminine poetic thinking in language. The aim is to identify the cognitive interpretation of spiritual experiences, social issues, women’s destiny, and life philosophy through flower names in the poet’s works.